2004
DOI: 10.1002/bies.20081
|View full text |Cite
|
Sign up to set email alerts
|

The ins and outs of lysophosphatidic acid signaling

Abstract: Lysophosphatidic acid (LPA) is a lipid mediator with a wide variety of biological actions, particularly as an inducer of cell proliferation, migration and survival. LPA binds to specific G-protein-coupled receptors and thereby activates multiple signal transduction pathways, including those initiated by the small GTPases Ras, Rho, and Rac. LPA signaling has been implicated in such diverse processes as wound healing, brain development, vascular remodeling and tumor progression. Knowledge of precisely how and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
487
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(507 citation statements)
references
References 89 publications
9
487
0
3
Order By: Relevance
“…Further downstream is Rac, a small GTP binding protein of the Rho family. Rac is a downstream affector in GPCR pathways that has been shown to be regulated by S1P [14] and LPA [15] and is known to induce cell motility via urokinase plasminogen activator (uPA) receptor induced actin cytoskeletal changes [16] and the loss of stress fibers as result of Rho inactivation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Further downstream is Rac, a small GTP binding protein of the Rho family. Rac is a downstream affector in GPCR pathways that has been shown to be regulated by S1P [14] and LPA [15] and is known to induce cell motility via urokinase plasminogen activator (uPA) receptor induced actin cytoskeletal changes [16] and the loss of stress fibers as result of Rho inactivation [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that ovarian tumors synthesize and secrete LPA, thereby increasing LPA levels in the ascitic fluid and serum of ovarian cancer patients (Xu et al, 1995;Andre et al, 2002). Furthermore, the growth factor like activity of LPA in stimulating cancer cell proliferation, migration, and invasiveness has been well documented (Moolenaar et al, 2004). Considering the importance of such LPA and LPAR-mediated autocrine and paracrine signaling pathways in tumor etiology and progression, there has been a major focus in identifying the G protein that couples LPARs to cell proliferation (Anliker and Chun, 2004).…”
mentioning
confidence: 98%
“…LPA is a phospholipid that is known to produce various cellular responses via stimulation of G protein families such as Gi, G12, and Gq [17][18][19] . Subsequent to the finding of high expression in ovarian cancer patients, LPA has been reported to be involved in processes in various cells that have an important effect on the development of cancer, such as proliferation, migration, and survival 20) .…”
Section: Discussionmentioning
confidence: 99%